2019
DOI: 10.1017/jns.2019.36
|View full text |Cite
|
Sign up to set email alerts
|

Is reduction in appetite beneficial for body weight management in the context of overweight and obesity? Yes, according to the SATIN (Satiety Innovation) study

Abstract: New dietary-based concepts are needed for treatment and effective prevention of overweight and obesity. The primary objective was to investigate if reduction in appetite is associated with improved weight loss maintenance. This cohort study was nested within the European Commission project Satiety Innovation (SATIN). Participants achieving ≥8% weight loss during an initial 8-week low-energy formula diet were included in a 12-week randomised double-blind parallel weight loss maintenance intervention. The interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Briefly, after an initial 8-week low-calorie diet (LCD) period, participants achieving ≥8% of weight loss were included in the subsequent 12-week randomized double-blind parallel intervention phase for weight lost maintenance (WLM), with food products designed to reduce appetite or matching control products as placebo. Detailed information about study design, visits, and methods has been previously published [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, after an initial 8-week low-calorie diet (LCD) period, participants achieving ≥8% of weight loss were included in the subsequent 12-week randomized double-blind parallel intervention phase for weight lost maintenance (WLM), with food products designed to reduce appetite or matching control products as placebo. Detailed information about study design, visits, and methods has been previously published [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The global prevalence of obesity has been sustainably increased over the past 40 years, from less 1% in 1975, to 6%-8% in 2016 [34]. Many factors were considered as the reason which induced obesity, such as genetic factors, environmental factors, abnormal endocrine regulation, in ammation and changes in intestinal ora changes [5]. Our study mainly discussed the effect of Chinese medicine on insulin resistance in obese mice study, the effect of TCM on insulin resistance in obese mice was studied.…”
Section: Discussionmentioning
confidence: 99%
“…There were many reasons for obesity, one of which was appetite. Appetite inhibition was a very effective way to treat obesity [5]. Intestinal hormones secreted by intestinal endocrine cells such as CCK, GLP-1 and peptide yy, had a regulatory effect on appetite, it has been found that combinations of gut-derived peptides (cholecystokinin (CCK), glucagon-like peptide-1 (GLP-1), peptide YY (PYY).)…”
mentioning
confidence: 99%
“…Crujeiras and colleagues ( 71 ) reported a similar pattern, with a decrease in ghrelin secretion after an 8-week hypocaloric diet (4.5 kg, 5% WL) being associated with an increased risk for weight regain [odds ratio = 3.109 ( P = 0.008) and r = −0.18 ( P = 0.061), respectively] in individuals with overweight or obesity at baseline (BMI = 30.7 ± 2.4 kg/m 2 ). Another study recently published by Hansen and colleagues ( 72 ) in individuals with overweight or obesity at baseline (BMI = 27.7 ± 2.1 kg/m 2 ) who had lost an average 9.6 kg (10.8%) also showed that a high level of appetite (assessed by visual analogue scales) after WL was not associated with WL maintenance at 3 months of follow-up (β = −0.02; P > 0.22; n = 181). However, the authors found that suppression of self-reported appetite (assessed with visual analogue scales) during the weight maintenance phase, by the consumption of food products high in fiber and/or protein, was associated with improved WL maintenance, making appetite-reducing food products an interesting strategy for the prevention of weight regain ( 72 ).…”
Section: Compensatory Responses To Weight Lossmentioning
confidence: 99%
“…Another study recently published by Hansen and colleagues ( 72 ) in individuals with overweight or obesity at baseline (BMI = 27.7 ± 2.1 kg/m 2 ) who had lost an average 9.6 kg (10.8%) also showed that a high level of appetite (assessed by visual analogue scales) after WL was not associated with WL maintenance at 3 months of follow-up (β = −0.02; P > 0.22; n = 181). However, the authors found that suppression of self-reported appetite (assessed with visual analogue scales) during the weight maintenance phase, by the consumption of food products high in fiber and/or protein, was associated with improved WL maintenance, making appetite-reducing food products an interesting strategy for the prevention of weight regain ( 72 ). Additionally, the marked reduction in leptin concentration that occurs with WL has also been reported not to be associated with weight regain in the long term in free-living humans ( 69 ).…”
Section: Compensatory Responses To Weight Lossmentioning
confidence: 99%